Panah, Panahli - (:unkn) unknown (My University, 2026)
Panah Panahli Hasan was born on August 30, 1957, in Saral Village, Republic of Armenia. He graduated from the local secondary school in 1974 and, in the same year, enrolled in the Faculty of Mechanics and Mathematics at Baku State University, from which he graduated in 1979. He began his professional career in 1979 as a Programmer and was later appointed Head of the Programming Department. In 1989, he joined the Institute of Mathematics and Mechanics of the Azerbaijan Academy of Sciences, where he worked as a Junior Researcher and later as a Senior Researcher. In 1994, he successfully defended his dissertation and was awarded the degree of Candidate of Physical and Mathematical Sciences (equivalent to Doctor of Philosophy (PhD) in Mathematics). From 2005, he served as the Director of the Physics and Mathematics Lyceum affiliated with the Azerbaijan University of Architecture and Construction. He currently holds the position of Associate Professor at the Department of Higher Mathematics of the Azerbaijan University of Architecture and Construction.